سەرى ڕێزمانى لە پێکهاتەى ڕستەدا - حسەین, ئازاد ئەحمەد (Sulaimani Journal for Humanities, 2021)
This research entitled (The Grammatical Head in Sentence Formation) is of special interest, because it shows the composition of the syntax components and the tools that participate in their formation. The research shows that the Kurdish language has a mixed system, in some formations (the head) is at the beginning and in others it is (the head) at the end. The grammatical head is classified according to the type of connection or relationship it forms into two groups: The first: which is the link between (the dictionary) and (Syntax(. The second: which is the relationship between (syntaxes units( The grammatical heads give the grammatical meaning of the lexical vocabulary (noun, adjective, verb) and give them different grammatical forms, for example : {(kteb / noun) ktebaka , ktebek , ktebakan{ )book / noun) the book ,one book , books.